Determination of Physicochemical, Rheological, Microbiological and Sensory Properties of Low Protein Yoghurt Substitutes Produced for PKU (Phenylketonuria) Patients - Fatma Çoşkun; Gizem Yıldız (Journal of Agricultural Sciences)
Treatment of PKU (Phenylketonuria) is a lifelong special diet program starting from the newborn period. The aim of this study was to produce yoghurt substitute for PKU patients. A commercial low protein milk substitute, xanthan gum (1%), commercial yoghurt gelling agent (1.5%), starch (4%) and pectin (1.6%) were used to produce yoghurt substitute. Control yoghurt was produced from cow's milk. The fermentation of all samples was completed at the end of the 5th hour. The pH of the samples decreased during storage. The total solid matter of the corn starch and pectin added samples were higher than the those of others. Syneresis values of the samples with xanthan gum, pectin and commercial gelling agent were negligible. The shear stress values of xanthan gum, commercial gelling agent and starch added samples were found close to each other. The shear stress of the pectin added sample was the highest among the samples. L* values of the control and starch added samples, a* and b* values of pectin added sample were higher than those of other samples. The amount of protein and phenylalanine was higher in the pectin added sample than the other samples containing gelling. However, their values in all yoghurt substitute samples were found to be well below the upper limit value that can be consumed. Although the amount of phenylalanine tolerated in the body varies according to age, gender, weight and the degree of phenylketonuria, it is stated that up to 1000 mg per day. While numbers of Lactobacillus delbrueckii ssp. bulgaricus increased during storage, numbers of Streptococcus thermophilus increased by pectin addition and decreased in other samples. In terms of general acceptability in sensory analyses, the most preferred sample was the sample added containing commercial gelling agent. This sample was followed by the samples with corn starch and pectin. It was concluded that these yoghurt substitutes could support the missing alternative product range for the patients.